Municipal Lex Contractus – Effectiveness of the Terms and Conditions for the Sale of Real Estate from the Municipal Real Estate Stock in Shaping the Real Estate Development Process - Słotwiński, Szymon (Review of European and Comparative Law, 2023)
The municipality, acting in the sphere of dominium, independently decides on the use and manner of use of individual assets. However, the trade in real estate constituting the subject of ownership of this local self-government unit requires compliance with a number of legal regulations, the most significant of which is the Act of August 21, 1997 on Real Estate Management (consolidated text Journal of Laws of 2021 item 1899, as amended). However, none of the provisions of the law refers explicitly to the freedom and limits of shaping by the municipality of the terms and conditions for the disposal of real estate, which in the case of a non-tender route are determined in negotiations conducted with the buyer, while in the case of a tender they are announced in the contract notice. The content established in this manner is then included in the protocol, which forms the basis for the conclusion of the contract, and thus directly affects the shape of the contractual legal relationship. The purpose of the publication will therefore firstly be to set out the legal framework for the municipality’s determination towards the future buyer of the real estate of the specific manner, in which the investment is to be carried out, as well as to answer the question as to the real possibility of the former owner (municipality) co-shaping the investment proces on the sold real estate after the buyer has signed the contract. The importance of the issue under consideration is expressed in the decision as to whether the creation by the municipality of its own lex contractus by means of the terms and conditions for the disposal of the real estate relating to specific deadlines for the commencement and completion of the investment process, the manner of use and development of the real estate, as well as the liability of the new owner towards the previous owner for their violation, is legally effective and can actually be enforced by the municipality.